MRGPRX2 ligandome: Molecular simulations reveal three categories of ligand-receptor interactions - Maier, Philip; Macht, Moritz; Beck, Silvan; Kolkhir, Pavel; Babina, Magda; Kremer, Andreas; Zahn, Dirk; Wolf, Katharina (Journal of Structural Biology, 2025)
Introduction: Mas-related G protein-coupled receptor (MRGPR) X2 is a mast cell receptor known to be activated by a wide range of ligands of various size, charge and origin. Our aim is to gain a deeper understanding of the binding processes of the different MRGPRX2 ligands and the ligand-receptor interactions in order to identify crucial structural elements for receptor activation. Materials and methods: We used the three-dimensional structure of MRGPRX2 described in Nature in 2021 by Cao et al. and Yang et al. to computationally model the interaction between MRGPRX2 and small molecule ligands under simulated physiological conditions. Results: Docking and post-docking samplings of the MRGPRX2 ligandome within the GPCR binding pocket led to the identification of key structural features for protein–ligand interactions. On the ligand side, we obtained an overlay of different molecular patterns or chemical groups by comparing different ligands plotted on the receptor. These key features include at least one protonated amine moiety of MRGPRX2 ligands contributing to one salt-bridge and one π-cation interaction, as well as an extended non-polar domain of the ligand surface that offer hydrophobic segregation and/or π-stacking interactions. In the receptor, we identified amino acids (GLU164, ASP184, PHE101, PHE170, TRP243, PHE244 and PHE257) that specifically interact via hydrogen bonding, salt-bridges, π-cation interactions and π-π stacking with the ligands to direct binding and ultimately receptor activation. Discussion: Our insights into ligand-receptor interaction obtained by molecular modeling can help to predict mast cell activation via MRGPRX2 including adverse reactions, and facilitate the development of MRGPRX2 antagonists for the treatment of mast cell-mediated diseases.
CRIS-Team Scopus Importer:2025-04-01
Keywords: Docking; Ligand-receptor interaction; Mas-related G protein coupled receptor X2; Molecular recognition; Pharmacophore

Smaller, Stronger, More Stable: Peptide Variants of a SARS-CoV-2 Neutralizing Miniprotein - Weißenborn, Lucas; Richel, Elie; Hueseman, Helena; Welzer, Julia; Beck, Silvan; Schäfer, Simon; Sticht, Heinrich; Überla, Klaus; Eichler, Jutta (International Journal of Molecular Sciences, 2022)
Based on the structure of a de novo designed miniprotein (LCB1) in complex with the receptor binding domain (RBD) of the SARS-CoV-2 spike protein, we have generated and characterized truncated peptide variants of LCB1, which present only two of the three LCB1 helices, and which fully retained the virus neutralizing potency against different SARS-CoV-2 variants of concern (VOC). This antiviral activity was even 10-fold stronger for a cyclic variant of the two-helix peptides, as compared to the full-length peptide. Furthermore, the proteolytic stability of the cyclic peptide was substantially improved, rendering it a better potential candidate for SARS-CoV-2 therapy. In a more mechanistic approach, the peptides also served as tools to dissect the role of individual mutations in the RBD for the susceptibility of the resulting virus variants to neutralization by the peptides. As the peptides reported here were generated through chemical synthesis, rather than recombinant protein expression, they are amenable to further chemical modification, including the incorporation of a wide range of non-proteinogenic amino acids, with the aim to further stabilize the peptides against proteolytic degradation, as well as to improve the strength, as well the breadth, of their virus neutralizing capacity.
CRIS-Team WoS Importer:2022-06-24
Keywords: SARS-CoV-2; virus; peptides; structure-based design; synthetic peptides; peptide mimics

The Effects of Conformational Sampling and QM Region Size in QM/MM Simulations: An Adaptive QM/MM Study With Model Systems - Paz, Holden; Beck, Silvan; Lee, Richmond; Ho, Junming; Yu, Haibo (Journal of Computational Chemistry, 2025)
Molecular properties in combined quantum mechanics and molecular mechanics (QM/MM) simulations have been shown to be dependent on the size of the quantum mechanical (QM) region and the amount of conformational sampling. Previous studies have largely focused on enzymatic systems, which have made it difficult to distinguish the effects of QM region size and conformational sampling from other factors including QM-MM boundary artifacts and the boundary effects. This study uses the difference-based adaptive solvation QM/MM method to investigate the tautomerization reactions of alanine and aspartate in explicit solvent. The choice of computationally tractable systems enables the decoupling of QM region size effects from other factors and a direct comparison of free energy surfaces with potential energy surfaces (PESs). The results show that (1) it is crucial to properly account for thermal fluctuations along the reaction pathways, and (2) free energy surfaces converge rapidly with increasing QM region size, whereas charge transfer requires a slightly larger QM region to achieve convergence. These findings are expected to guide future studies of enzymatic systems and other complex systems where QM/MM methods are applied.
CRIS-Team Scopus Importer:2025-05-09
Keywords: Adaptive QM/MM; Combined QM/MM; Minimum Energy Paths; Potential of Mean Force; QM Region Size